SATIRE IN ZOOTOPIA BY RICH MOORE AND BYRON HOWARD - Nurul Hidayani; Widiarsih Mahanani (LINGUAMEDIA Journal, 2022)
This research deals with analysis of satire and utopia condition in Zootopia by Rich Moore and Byron Howard. This research aims to find out the type of satire and to know the kind of utopia condition reflected in Zootopia. The writer uses types of satire theory by Abrams & Harpham (2014) and utopia theory by More in Dutton (2014). The qualitative descriptive method is applied as the research method in analyzing the data. The data focus in Zootopia film that consists of satire and utopia condition.Based on the analysis, the writer finds the three types of satire, i.e. Horation satire, Juvenalian satire, and Menippean satire found within the film. From the data are obtained, Zootopia is categorized as Juvenalian satire because it is the dominant data because almost all of characters use harsh words and straight to the point in delivering the message. The messages that are conveyed with harsh language make the audience feels angry because it can touch the conscience. Thus, it makes realize how important it is to respect differences and tolerance the others.There were data of utopia conditions depicted by the situation in Zootopia. Zootopia is portrayed as a place where someone lives with each other in peace, tolerance for existing differences, and the realization of dreams, where everyone has same equality and right to be whatever they want.  Keywords: Horation satire, Juvenalian satire, Menippean satire, satire, film, utopia, Zootopia.